PENGEMBANGAN E-MODUL PRAKTIKUM KELISTRIKAN OTOMOTIF BERBASIS SELF DIRECTED LEARNING PADA PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNS - Agrippina Gian Pangestu; Ranto Ranto; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
Technology has created numerous benefits in various aspects of life, including education. Teachers and students should integrate technology into their learning plans to ensure effective teaching and learning. The use of technology in education can inspire students to pursue new interests and motivate them to engage in learning activities that enhance their perspectives. The role of an instructor in a student's education is crucial. Self-directed learning (SDL) is an instructional process that requires students to identify their own learning needs, provide resources, and practice learning techniques. By using the right methods and situations in teaching, students can develop their own skills and enhance their learning experience. This study aims to improve the effectiveness of e-module practical on the otomotif kelistrikan in the Mesin Technical Education program.The study on the development of an e-module for otomological pedagogy found that the validity of the e-module met good results with validity scores of 84.4% (very feasible) for material, 85% (very feasible) for media, 75% (feasible) for language, and 83,3% very (feasible) for data from student responses. Critics and respondents also deemed that improvements are needed for the e-module. The results were based on feedback from the committee of otomologists who provided some suggestions about the electronic pedagogical pedagogy module in terms of quality and safety, indicating that improvements are still needed for this module. The e-module will be distributed through the Mesin Technical Education Program at the University of Surakarta.Keywords: development, e-modules, self directed learning